Toward a roadmap for addressing today's health dilemma–The 101-statement consensus report - Wirnitzer, Katharina C.; Motevalli, Mohamad; Tanous, Derrick R.; Drenowatz, Clemens; Moser, Maximilian; Cramer, Holger; Rosemann, Thomas; Wagner, Karl-Heinz; Michalsen, Andreas; Knechtle, Beat; Fras, Zlatko; Ritskes-Hoitinga, Merel; et al. (Frontiers in Nutrition, 2025)
ImportanceIn recent decades there has been an expansion in the quantity and quality of scientific findings and guidelines on different health topics to promote individual and public health status. Reports also indicate that there has been a simultaneous increase in the financial burden of disease, including trillions spent on healthcare resources by governments worldwide (predominantly in developing countries) to address health concerns. At the same time, personal health behavior is well-known as efficient and cost-free, holding four times the potential to prevent early death compared to health care. Despite this knowledge, data show that the increasing prevalence of unhealthy lifestyles and the associated chronic diseases, especially in Western societies, still need to be controlled. This circumstance exemplifies today‘s global health dilemma, which alarms the inadequacy of ongoing efforts to address the existing health concerns worldwide.Setting, insights, and observationsThree international, multidisciplinary, and inter-university events (two scientific conferences and one tertiary education symposium) were held in Austria (Innsbruck) between 2020 and 2022 to discourse, discuss, and debate these concerns. Two hundred eighty-four experts from 76 universities, organizations, and stakeholders spanning 31 nations and five continents participated in this international research and knowledge exchange to address today's global health dilemma. The latest scientific findings were discussed to develop practical strategies for improving lifestyle behavior and focus on the dual “Healthy Eating & Active Living” approach as a minimum recommendation for sustainable lifelong health and care. The expert panel debated crucial research priorities and future policies, identified gaps and untapped potential in basic health approaches that have been grossly neglected, and approved the evidence-based 101 consensus statements presented.Conclusions and relevanceThese endeavors aim to develop novel and effective interventions that address the needs of individuals and communities and promote optimal health status.